Diagnosis and Management of Vestibular Neuritis - Clarissa Fiolly Refieska; Rossy Rosalinda (Fakultas Kedokteran Universitas Andalas, 2026)
Diagnosis and Management of Vestibular Neuritis Background: Vestibular neuritis is one of the most common peripheral vestibular disorders, characterized by the sudden loss of unilateral vestibular function, resulting in acute vertigo without associated cochlear or neurological symptoms. Objective: To know and understand the diagnosis and management of vestibular neuritis. Literature Review: The exact etiology of neuritis vestibular remains unclear, but three main mechanisms are thought to play a role viral infection of the vestibular nerve, ischemia of the anterior vestibular artery, and immunological mechanisms. The clinical findings of neuritis vestibular include sudden-onset severe spinning vertigo lasting more than 24 hours, often accompanied by nausea and vomiting, typically occurring in middle-aged individuals, without cochlear symptoms or other neurological manifestations. Accurate diagnosis of neuritis vestibular requires supportive examinations such as the head impulse test (HIT), caloric test, and vestibular-evoked myogenic potential (VEMP) Treatment for vestibular neuritis includes symptomatic therapy, specific pharmacological therapy, and vestibular rehabilitation, which have been studied and applied to reduce symptoms, accelerate vestibular compensation, and improve patients’ quality of life. Conclusion: Vestibular neuritis, also known as vestibular neuronitis, is a distinctive form of peripheral vertigo and a major cause of acute vestibular dysfunction. Its etiology remains uncertain but is thought to involve viral infection, ischemia, and immunological mechanisms. Clinically, the main symptom is severe spinning vertigo lasting more than 24 hours, often accompanied by nausea and vomiting in middle-aged patients. Diagnosis is established through physical examination and ancillary tests. Treatment consists of specific pharmacological therapy and vestibular rehabilitation.